2020
DOI: 10.3389/fpsyg.2020.02028
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality, Sleep Structure, and PER3 Genotype Mediate Chronotype Effects on Depressive Symptoms in Young Adults

Abstract: Depression and its related mood disorders are a major global health issue that disproportionately affects young adults. A number of factors that influence depressive symptoms are particularly relevant to the young adult developmental stage, including sleep loss, poor sleep quality, and the tendency toward eveningness in circadian preferences. However, relatively few studies have examined the relationship between sleep and circadian phenotypes, and their respective influences on mood, or considered potential mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 91 publications
2
13
1
Order By: Relevance
“…In other words, PER3 5/5 individuals tended to sleep late or be awake at night (nocturnal). This is inconsistent with previous studies, which suggested that PER3 5/5 carriers tend to go to bed earlier and wake earlier than those with PER3 4/4 (Hida et al, 2014;Pereira et al, 2005;Viola et al, 2012;Weiss et al, 2020). Unfortunately, our present data do not allow us to detect the reasons, there may be other unknown mechanisms or genes involved in sleep latency.…”
Section: The Per3 Vntr Gene Polymorphism Impact Of Sleep Qualitycontrasting
confidence: 99%
“…In other words, PER3 5/5 individuals tended to sleep late or be awake at night (nocturnal). This is inconsistent with previous studies, which suggested that PER3 5/5 carriers tend to go to bed earlier and wake earlier than those with PER3 4/4 (Hida et al, 2014;Pereira et al, 2005;Viola et al, 2012;Weiss et al, 2020). Unfortunately, our present data do not allow us to detect the reasons, there may be other unknown mechanisms or genes involved in sleep latency.…”
Section: The Per3 Vntr Gene Polymorphism Impact Of Sleep Qualitycontrasting
confidence: 99%
“…Importantly, there is no association between chronotype and PER3 polymorphism ( Silva A. et al, 2020 ). This conclusion may arise because the gender-specific effects of chronotype and depression were overlooked ( Weiss et al, 2020 ). Other scholars also identified PER3 mutations associated with chronotype and anxiety ( Liberman et al, 2017 ).…”
Section: The Differences Between Chronotypes and The Association With...mentioning
confidence: 99%
“…A potential explanation is the gender difference in melatonin, sex hormones, and behavioral and psychological factors (sleep quality, alcohol intake) ( Kim et al, 2020 ). In addition, the circadian gene PER3 variable number of tandem repeats was independently related to chronotype only in males ( Weiss et al, 2020 ). Taken together, both the chronotype and psychiatric disorders showed significant sex-specific effects, although the causes and mechanisms are unclear.…”
Section: The Differences Between Chronotypes and The Association With...mentioning
confidence: 99%
“…Per3 VNTR variants are associated with circadian preferences, non-visual responses to light, and brain and cognitive responses to sleep deprivation/circadian rhythm dysregulation. Per3 5/5 carriers are more likely to go to bed early and wake up earlier than Per3 4/4 carriers [ 53 , 54 , 55 ]. Cheng et al [ 56 ] reported that the Per3 5/5 genotype was associated with an increased risk of daytime sleep disturbance in night shift workers.…”
Section: Discussionmentioning
confidence: 99%